(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This study will examine how science, technology, and mathematics (STM) can solve insecurity and economic problems in southwest Nigeria. The study employed a survey research design. The total population of this study consisted of 5,670 people, of which 3,789 were randomly selected across the five states in southwest Nigeria. The instruments used were a structured questionnaire titled Science, Technology and Mathematic Tool for Solving Insecurity and Economics Problems in South-West Nigeria Rating Scale (STMTSIEPRS) (r=0.85). Three research questions were formulated and tested. Data were analysed using Multiple Regression. The results revealed a significant primary influence of Science, Technology and Mathematics on Economic insecurity in South-West Nigeria with (R = .258 and a multiple R2 of .066). Also, it revealed the relative contribution of two dependent variables to the independent variables, expressed as beta weights, vis insecurity (beta equals .006, t= 5.178) and economic problems (beta equals .419,β = .419, 5 t = 5.086). It was therefore concluded that Mathematics, Science and Technology play a major role in the economic advancement of a community and as well can enhance strong security if adequately utilized. It was recommended that the Government fund researches on Science, Technology and Mathematics to end economic recession and insecurity.